Reliability of the Cutting Alignment Scoring Tool (CAST) to Assess Trunk and Limb Alignment During a 45-Degree Side-Step Cut - Lauren S Butler; Eryn K Milian; Amie DeVerna; Kevin Latz; Henry B Ellis; Alexa R Martinez; Kristin Hayden; Christian Gerstenkorn; Sara C Carpenito; Charles W Wyatt; Dai Sugimoto (International Journal of Sports Physical Therapy)
# Background